2022
DOI: 10.1001/jamanetworkopen.2022.15681
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Receipt of Smoking Cessation Assistance Within the US

Abstract: This cross-sectional study analyzes sociodemographic variations in receiving smoking cessation assistance from health professionals by individuals who reported smoking, or quitting, within the past year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 5 publications
(6 reference statements)
0
7
0
Order By: Relevance
“…states), 3 indicating a similar LCS prevalence rate in 2021 and 2022 (19.6%). A limitation of our study was that BRFSS LCS data are self-reported.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…states), 3 indicating a similar LCS prevalence rate in 2021 and 2022 (19.6%). A limitation of our study was that BRFSS LCS data are self-reported.…”
Section: Discussionmentioning
confidence: 75%
“…2 Despite recommendations, LCS uptake has been low, with 2021 data from 4 states reporting 21% of eligible individuals screened. 3 National estimates of LCS prevalence are limited. Hence, we sought to compare LCS prevalence in 2022 by sociodemographic characteristics and by state among individuals eligible per 2013 vs 2021 USPSTF recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…The ACR Lung Cancer Screening Registry estimated that the national rate of LCS was only 5% in 2018, although it varied significantly by state 39 . The most recent LCS rates come from four US states that included LCS questions in the Behavioral Risk Factor Surveillance System in 2021 126 . Individuals eligible for LCS reported recent screening ranging from 17.5% in New Jersey to 30.3% in Rhode Island 126 …”
Section: Discussionmentioning
confidence: 99%
“…The most recent LCS rates come from four US states that included LCS questions in the Behavioral Risk Factor Surveillance System in 2021 126 . Individuals eligible for LCS reported recent screening ranging from 17.5% in New Jersey to 30.3% in Rhode Island 126 …”
Section: Discussionmentioning
confidence: 99%
“…5 However, there is still a possibility that we fail to capture key variables, particularly because lung cancer risk model variables tend to overestimate risk with an expected-observed ratio range of 0.83 to 3.69 and possess lower areas under the curve, ranging from 0.62 to 0.75. 7 Second, given a recent study showing the association between having a primary health care professional and an increased likelihood of lung cancer screening, 8 health care accessibility can be a pivotal determinant in clinical contexts while it is ensured in RCTs by design. Third, variability in adherence to lung cancer screening between the RCTs (>90% and >95% in NELSON and the NLST, respectively) and general populations (pooled adherence of 57% among 21 studies 9 ) also merits attention.…”
Section: + Related Articlementioning
confidence: 99%